Modification of powdered activated carbon for the production of Carbon Nanofibers (CNFs) - Ahmed, Yehya M.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Jameel, Ahmed Tariq; AlSaadi, Mohammed A. (2009)
In the present work, powdered activated carbon (PAC) was modified and used for the production of carbon nanofibers (CNFs). The modification of PAC was done by the impregnation of nickel on the surface of the activated carbon using the wet impregnation method. Variable weight percentage ratios of the catalyst (nickel) ratio were used. The nanofibers were synthesized on the surface of modified PAC by using the Chemical Vapor Deposition (CVD) method at a Temp. of ~ 680º C for one hour in the presence of acetylene as a carbon source. FESEM, TEM, and TGA were used for the characterization of the produc